Sovereignty in Foucault’s Courses at the Collège de France: Peer-reviewed article (Italian Review of Legal History, 2022)
Of all the legal and political topics, sovereignty is the most prominent in the courses Michel Foucault taught at the Collège de France from 1970 to 1984. Teaching at this institution - entitled, in his case, History of Systems of Thought - obeys particular rules. One of these is the obligation incumbent on professors not to repeat, from year to year, the same course of lectures given previously, but to change the subject. Apart from this clause, in the years from 1973 to 1979, Foucault repeatedly and intensively deals with issues that have a very explicit and direct connection to the dimension of power. Some of the courses he taught form the basis of works he published in this period such as Discipline and Punish or The Will to Knowledge. It is, of course, within these courses that the idea of power that runs through his research in this temporal phase takes shape, and it is thanks to this transparent laboratory of his work that it is possible to follow the analysis and reworking that he carries out on the subject of ‘sovereignty’. Although this term is never explicitly present in the titles of the teaching years, many of the lessons that engage Foucault’s teaching converge on this category. Foucault receives from legal theory and political science a word to which a precise meaning is peacefully attributed. The holder of sovereign power is represented, by a very long and important tradition, as the one around whom the functioning of the state revolves. The sovereign is placed ‘at the top’ and ‘at the centre’ of the map of power as the point from which and towards which all the essential cogs that make the state machine work move. Moreover, the sovereign is the one who exercises his power through the use of eminent force, suitable to enforce laws, maintain order and inhibit any hypothesis of sedition. Foucault intends, conversely, to question this reading. The itinerary he follows points towards a phenomenology of power relations captured in their multiformity and dissemination. It is a matter of observing power by renouncing the perspective of verticality, as if it was located in a single place, the perspective of patrimoniality, as if it was owned exclusively by someone, and, finally, the perspective of repression, as if the only language it could speak was that of intimidation, sanction and weapons. In order to reread power, one must, on the contrary, study its functioning in the partial apparatuses of society, transversally distributed and capable of implementing a technology that is not based on interdiction but, on the contrary, on the solicitation of discipline. Along his itinerary, Foucault encounters the historical development of penality, within the perimeter of which a strongly individualising power is developing, capable of pursuing a pigeon-holing of individuals that makes use of multiple techniques of observation and description operating at various levels of the social structure; the history of psychiatry, thanks to which the normal/abnormal distinction, and the consequent measures of monitoring and control of deviant conduct, have been able to avail themselves of the use of ‘scientific’ and, therefore, more cogent parameters; lastly, biopolitics, which has relocated the theme of the subjection of bodies to rules and constraints, with a view to maximising their performance, from the scale of individuals to that of populations, leaving to appear behind the tralativist figure of the sovereign who expresses his hegemony by deciding who can live and who must die, the much more concrete image of the anonymous power of the rules of nutrition, hygiene and prophylaxis that establish how an entire community must be cared for and protected.
Keywords: State; sovereignty; war; disciplines; biopolitics